JORDAN GENERALIZED DERIVATIONS ON ïM-MODULES - Salih, Salah Mehdi (MAGISTRA, 2016)
The aim object of this paper is present the definitions of generalized drivation, Jordan generalizedderivation and Jordan generalized triple derivation of ï-rings into ï-module also we prove that every Jordangeneralized derivation of Î-ring M into 2-torsion prime ïï-module X is a derivation of M into X. MathematicsSubject Classification: 16W30, 16U80.Keywords: ïï-module, Jordan generalized derivation.